2016
DOI: 10.1089/rej.2015.1717
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cell Cycle Re-Initiation in DNA Damage Response of Post-Mitotic Cells and Its Implication in the Pathogenesis of Neurodegenerative Diseases

Abstract: Neurodegenerative diseases are often associated with both normal and premature aging. Resumption of the cell cycle by neurons induced by DNA damage may lead to their apoptosis, which contributes to the degeneration of neuronal tissue. Cell cycle and DNA replication proteins are frequently found in patients with neurodegenerative diseases. Oxidative stress, which is considered to play an important role in aging and pathogenesis of many neurodegenerative diseases, can induce DNA damage and stimulate cell cycle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 122 publications
1
14
0
Order By: Relevance
“…Together, these findings support an active role of RAS‐dependent cell cycle re‐entry and DDR in promoting the toxic effects of expressing aSyn in quiescent yeast cells and by extension in postmitotic mammalian neurons. This is consistent with emerging models of the toxic effects of cell cycle re‐entry in synucleinopathies and other neurodegenerative disorders (Sharma et al, ; Tokarz et al, ). Postmitotic cells may enter the cell cycle in response to stress signals induced by the accumulation of toxic forms of aSyn, perhaps as part of an aborted attempt to replace dying cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Together, these findings support an active role of RAS‐dependent cell cycle re‐entry and DDR in promoting the toxic effects of expressing aSyn in quiescent yeast cells and by extension in postmitotic mammalian neurons. This is consistent with emerging models of the toxic effects of cell cycle re‐entry in synucleinopathies and other neurodegenerative disorders (Sharma et al, ; Tokarz et al, ). Postmitotic cells may enter the cell cycle in response to stress signals induced by the accumulation of toxic forms of aSyn, perhaps as part of an aborted attempt to replace dying cells.…”
Section: Discussionsupporting
confidence: 89%
“…However, the normal physiological functions of aSyn as well as the nature of the cytopathic effects of aSyn overexpression and mutations remain incompletely understood. An emerging body of evidence suggests that cell cycle aberrations, including inappropriate re‐entry into the cell cycle, are linked to the pathological effects of aSyn (Sharma et al, ; Tokarz, Kaarniranta, & Blasiak, ). For example, elevated levels of proteins involved in cell cycle re‐entry and DNA synthesis in dopaminergic neurons are observed in the brain of PD patients (Hoglinger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, we here emphasize that neither the incidence nor the prevalence of dementia has turned out to be a mere function of age, as discussed above. Second, it is important to understand that the adult human nervous system, including the brain, is composed entirely of post-mitotic cells (i.e., cells which cannot divide and therefore cannot replace themselves), and is therefore more vulnerable to cumulative oxidative stress (as such cells must endure a lifetime of free radical injury because they are not replaced [86], thereby rendering a healthy neurocognitive system particularly dependent upon antioxidants that can and do cross the blood-brain barrier, e.g., vitamin C, L, Z) [87]. In other words, there is a sound rationale to postulate that the interaction of the aging brain and lifelong nutrition (rather than merely the aging brain, and notwithstanding other and acknowledged risk factors, such as genetic background) represents a determinant of whether and/or when a person goes on to develop dementia.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of several pathways associated with DNA replication and p53-(in)dependent DNA damage responses and checkpoints were correlated with CT changes. DNA replication during the S-phase may control the survival of post-mitotic cells by DNA repair mechanisms or apoptosis followed by DNA damage, which seems to be the case in neurodegenerative diseases (Tokarz et al, 2016). Furthermore, DNA damage response signaling can be modulated by tumor suppressor p53 and may also contribute to apoptosis in aging and age-related neurodegenerative disorders (Mohammadzadeh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%